Steady State Analysis of Non-Isolated Single-Input Multi-Output SEPIC Converter for Stand-alone Applications - C. Anuradha; N. Chellammal; S. Vijayalakshmi; R. C. Ilambirai (Institute of Advanced Engineering and Science, 2018)
This paper proposes a non-isolated three port SEPIC converter for stand-alone photovoltaic applications. The proposed topology uses the Single Input Multi Output (SIMO) structure. This topology consists of a single photovoltaic source as input and it is a unidirectional power converter. Mathematical analysis for the proposed system is performed and simulations are carried out using MATLAB/Simulink. The design parameters of capacitors and inductors are calculated from small ripple analysis. The simulation analysis for the proposed open loop topology is verified using a real time hardware setup.The entire process is carried out in Continuous Current Mode (CCM) of operation. The experimental results for hardware are verified with simulations and compared.